Knowledge, Attitudes Regarding Dental and Oral Health With The Number of Funtioning Teeth: A Cross-Sectional Study - Tharienna Zalfa Haidee; Imam Sarwo Edi; Agus Marjianto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Background: Elderly people are expected to have a minimum of 20 functioning teeth so that mastication, speech, and aesthetic functions are assumed to be normal. However, in reality, tooth loss still occurs in some elderly people, so they only have less than 20 functioning teeth. Problem: Low percentage of functioning teeth in the elderly. Research Objective: To determine the relationship between knowledge and attitudes about dental and oral health with the number of functioning teeth in the elderly at Integrated Service Post Melati VI, Karanglo Village, Mojowarno District, Jombang Regency. Method: This type of research is cross-sectional analytical research. The sample of respondents was 52 elderly people. The research instrument to measure knowledge and attitudes about dental and oral health in the elderly uses a questionnaire sheet and a dental examination sheet to identify the number of functioning teeth. The data obtained were analyzed using non-parametric tests with chi square. Results: There was no relationship between knowledge about dental and oral health and the number of functioning teeth. There is a relationship between attitudes about dental and oral health and the number of functioning teeth (study at the Melati VI Integrated Service Post for the Elderly, Karanglo Village, Mojowarno District, Jombang Regency, 2024)